A study on the perception of librarians on property accountability and its applicability to the practice of the library profession - Quintos, Kate Lora M. (2005)
Librarians manage the library, as well as give diligent care for the collection and try to secure the collection. They try their very best to perform all their tasks. They serve the patrons to the best of their abilities. This paper aims to disclose the perceptions of librarians to property accountability and its effect to the library service. The threat and occurrence of losses and theft are inevitable in any library. Librarians shoulder the responsibility over their collection called property accountability.